IMPACT OF MOBILE APPLICATION-BASED LEARNING ON ENGLISH LISTENING SKILL DEVELOPMENT AMONG POLYTECHNIC STUDENTS IN TAMIL NADU - Flowerns. J, Jesinth; K. Sufina (ShodhKosh: Journal of Visual and Performing Arts, 2026)
English as a language has displayed absolute dominance and anarchic destruction of local regional languages across the world. It has been accepted that English is the universal accepted language for communication for business and professional activities. This continued domination of English has its deepened effects on India and its official communication with the world. It could be seen that English still remains with its undisputed authority and dominance in its communicating link with the world. It could also be seen that this has led to the total destruction of local Indian languages which has left the country and from the people’s mind. English is still the official language for social, professional & business communication across the country. This has also created a pre requisite to read, learn & master this language for proficiency and communication in all official & business platforms. Engineering is a global program also when read in Indian curriculum – the need for learning in English as the platform remains questionable, challenging & intriguing. This research is an exploratory & conclusive research on the problems and issues which prevail in mobile based English learning & listening skill development language for business correspondence & communication among polytechnic students. The nature and extent of problems associated with it would also be studied. The impact of mobile based English on polytechnic student’s professional career would also be examined. Suitable strategies and solutions for excellence in mobile English language learning for listening skill development among polytechnic students towards 2030 would also be provided. In this study Primary data would be collected from 30 polytechnic students studying various diploma courses in Government Polytechnic College, Sevvapet, Thiruvallur district, Tamil Nadu. The continued challenges and problems in polytechnic students for mobile English learning&listening skill development as a student would also be explored. Also, the Questionnaire is used to collect the data, which could bring in more authentic information on this domain. The Data analysis would be done with a SPSS as the suitable strategies and solutions for mobile English learning & listening excellence for polytechnic students would be provided.